Effects of Respiratory Rate, Plateau Pressure, and Positive End-Expiratory Pressure on PaO2 Oscillations after Saline Lavage - Baumgardner, James E; Markstaller, Klaus; Pfeiffer, Birgit; Doebrich, Marcus; Otto, Cynthia M (American journal of respiratory and critical care medicine, 2002)
One of the proposed mechanisms of ventilator-associated lung injury is cyclic recruitment of atelectasis. Collapse of dependent lung regions with every breath should lead to large oscillations in PaO2 as shunt varies throughout the respiratory cycle. We placed a fluorescence-quenching PO2 probe in the brachiocephalic artery of six anesthetized rabbits after saline lavage. Using pressure-controlled ventilation with oxygen, ventilator settings were varied in random order over three levels of positive end-expiratory pressure (PEEP), respiratory rate (RR), and plateau pressure minus PEEP (Delta). Dependence of the amplitude of PaO2 oscillations on PEEP, RR, and Delta was modeled by multiple linear regression. Before lavage, arterial PO2 oscillations varied from 3 to 22 mm Hg. After lavage, arterial PO2 oscillations varied from 5 to 439 mm Hg. Response surfaces showed markedly nonlinear dependence of amplitude on PEEP, RR, and Delta. The large PaO2 oscillations observed provide evidence for cyclic recruitment in this model of lung injury. The important effect of RR on the magnitude of PaO2 oscillations suggests that the static behavior of atelectasis cannot be accurately extrapolated to predict dynamic behavior at realistic breathing frequencies.